Maternal depression during pregnancy and the postnatal period: risks and possible mechanisms for offspring depression at age 18 years. - Pearson, R; Evans, J; Kounali, D; Lewis, G; Heron, J; Ramchandani, P; O'Connor, T; Stein, A (2013)
IMPORTANCE: Some small studies suggest that maternal postnatal depression is a risk factor for offspring adolescent depression. However, to our knowledge, no large cohort studies have addressed this issue. Furthermore, only 1 small study has examined the association between antenatal depression and later offspring depression. Understanding these associations is important to inform prevention. OBJECTIVE: To investigate the hypothesis that there are independent associations between antenatal and postnatal depression with offspring depression and that the risk pathways are different, such that the risk is moderated by disadvantage (low maternal education) with postnatal depression but not with antenatal depression. DESIGN, SETTING, AND PARTICIPANTS: Prospective investigation of associations between symptoms of antenatal and postnatal parental depression with offspring depression at age 18 years in a UK community-based birth cohort (Avon Longitudinal Study of Parents and Children) with data from more than 4500 parents and their adolescent offspring. MAIN OUTCOMES AND MEASURES: Diagnosis of offspring aged 18 years with major depression using the International Classification of Diseases, 10th Revision. RESULTS: Antenatal depression was an independent risk factor. Offspring were 1.28 times (95% CI, 1.08-1.51; P = .003) more likely to have depression at age 18 years for each standard deviation increase in maternal depression score antenatally, independent of later maternal depression. Postnatal depression was also a risk factor for mothers with low education, with offspring 1.26 times (95% CI, 1.06-1.50; P = .01) more likely to have depression for each standard deviation increase in postnatal depression score. However, for more educated mothers, there was little association (odds ratio, 1.09; 95% CI, 0.88-1.36; P = .42). Analyses found that maternal education moderated the effects of postnatal but not antenatal depression. Paternal depression antenatally was not associated with offspring depression, while postnatally, paternal depression showed a similar pattern to maternal depression. CONCLUSIONS AND RELEVANCE: The findings suggest that treating maternal depression antenatally could prevent offspring depression during adulthood and that prioritizing less advantaged mothers postnatally may be most effective.